Analysis of Rotator Cuff Injury in Tennis Players Using Long Racket versus Short Racket - Khan, Barirah; Khan, Yasir; Tariq, Zayad; Aamir, Shabnum; Ahmad, Waqar; Ahmed, Zaheer (ADVANCES IN BASIC MEDICAL SCIENCES, 2020)
Background: Tennis is a famous recreational sport worldwide; however, it involves numerous abrupt and distinct body movements that may lead to severe musculoskeletal injuries to the player. Most common musculoskeletal injuries in tennis are overuse injuries of wrist and elbow. But certain factors may also put stress on other body parts, for instance, shoulder and calf regions. The aim of the study was to find out association of rotator cuff injury with length of rackets among tennis players. Methodology: This analytical association study was conducted in Shahina Jamil Hospital - Frontier Medical College, Abbottabad and King Abdullah Teaching Hospital, Mansehra. Inclusive criteria were fulfilled by recruiting tennis players from different clubs and universities. Data was collected after taking informed consent through convenient non-probability sampling technique. Hawkins-Kennedy test was used to assess the rotator cuff tendinitis. Results: The results showed that the age and experience have a consistent relationship with the racket lengths, with older and more experienced participants using long racket frequently. However, the probability (p-value) of association of rotator cuff injury and length of rackets used by tennis player was 0.488, indicating that rotator cuff injury is not dependent on the length of the racket used by tennis players. Conclusion: There was no significant association between rotator cuff injury with the length of long and short rackets in tennis players. The probability of injury may depend on the body mechanics of the player. Keywords: Pain, Rotator cuff, Shoulder joint, Sports, Tennis, Overuse injuries, Musculoskeletal, Racket/Racquet length